Moderated-Mediation Roles: Relationship between Internet Addiction, Neuroticism, Perceived Stress, and Adaptive Coping Style among Indonesian Migrant Workers in Taiwan - Simanjutak, Erni Julianti; Ko, Huei-Chen (UI Scholars Hub, 2021)
This study examined the relationship of neuroticism and internet addiction by investigating the mediating role of perceived stress and the moderating role of adaptive coping style among Indonesian migrant workers in Taiwan. The study was conducted with a cross-sectional design on 466 migrant Indonesian workers collected in Indonesian working places and the leisure activity places in Taipei and Taichung area in Taiwan by purposive sampling. Participants completed a survey, including measures of neuroticism, internet addiction, perceived stress, and adaptive coping style. The results showed that perceived stress mediated the association of neuroticism with internet addiction. Furthermore, adaptive coping style moderated the strength of the mediation between neuroticism and internet addiction via perceived stress, such that the mediated relationship weakened under the higher levels of adaptive coping style than under the lower levels of adaptive coping style. These results supported the hypothesized model. However, the model needs further examination in a large-scale longitudinal study.